Factores que afectan el rendimiento académico en estudiantes de educación básica elemental en la Unidad Educativa Emigdio Esparza Moreno cantón Babahoyo, Provincia Los Ríos - Santana Santillan, Gina Roxana (2020)
The investigation Factors that affect the academic performance in elementary basic education students in the educational unit “Emigdio Esparza Moreno, of the Babahoyo canton, province of Los Ríos, arises from the low academic level demonstrated in the poor grades and in the motivation that students have for learning The purpose is to detect the main causes and propose alternative solutions. For this purpose, theoretical information was obtained from bibliographies such as texts, scientific articles and theses that allowed us to better understand the subject. For the collection of information, investigations of type were used: diagnostic, explanatory and descriptive, the methods used are inductive, deductive, hypothetical and analytical. Information about the problem was obtained from interviews and surveys that were applied to students, parents, managers and teachers of the institution. Statistical procedures were applied, such as the Chi-square test to assess the hypothesis where the problem of low performance is determined, is mainly due to family and pedagogical factors, and the application of workshops with motivational teaching strategies that help students teacher to arouse interest in the class. The proposal is addressed to teachers because there was evidence of dissatisfaction on the part of the students for their teaching methodology and also the lack of concern of parents at home. The purpose is to make the teacher improve his pedagogical practice and in the classroom help to solve the learning deficit since at home they do not have enough support.